2014
DOI: 10.14260/jemds/2014/2856
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Morphology of the Glenoid Cavity

Abstract: AIM:A morphometric study of the glenoid cavity of 80 adult dry human scapulae in North Indian Population was done to evaluate the various parameters of the glenoid cavity. MATERIAL AND METHODS:This study was done on 80 dry, unpaired adult human scapulae (41 right & 39 left) of unknown sex belonging to the North Indian population. Maximum superior-inferior diameter and Maximum anterior-posterior diameter of the glenoid cavity were measured and Glenoid cavity index was calculated. The shape of the glenoid cavity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 8 publications
4
11
3
Order By: Relevance
“…Polguj M et al [15] noted the combined GCI to be 72.35±5.55, which was higher than the present study. The mean cavity index of 70.37±4.08% on right side while 68.59±4.36% on left side recorded by Dhindsa et al [16] were found very close to present study.…”
Section: Discussionsupporting
confidence: 90%
“…Polguj M et al [15] noted the combined GCI to be 72.35±5.55, which was higher than the present study. The mean cavity index of 70.37±4.08% on right side while 68.59±4.36% on left side recorded by Dhindsa et al [16] were found very close to present study.…”
Section: Discussionsupporting
confidence: 90%
“…Middernacht et al [8] noted it as 37.3 mm and Coskun et al [9] as 36.3 mm. (Table 3) The mean AP1 diameter measured as the maximum diameter in the lower half of glenoid cavity was 24 mm in the present study which is similar to the observations by Mamatha et al [1] (23.2 mm), Rajput et al [6] (23.11 mm) and Dhindsa et al [7] (23.70 mm). Middernacht et al [8] observed it as 27.9 mm and Coskun et al [9] as 24.6 mm.…”
Section: IVsupporting
confidence: 91%
“…[6] The mean height of the glenoid cavity in the present study was 35.16 mm, Mamatha et al [1] observed it as 33.79 mm, Rajput et al [6] as 34.59 mm. and Dhindsa et al [7] as 34.24 mm. Middernacht et al [8] noted it as 37.3 mm and Coskun et al [9] as 36.3 mm.…”
Section: IVmentioning
confidence: 79%
“…The data were then entered and analysed using the Microsoft Excel 2010. Dhindsa GS et al (2014) [15] Patil et al (2014) [17] Present study (2015) The present study was performed on dry human scapulae. The comparison of data between present study and previous studies found several differences as well as similarities in the dimensions of the scapula and glenoid cavity (Table 3).…”
Section: Methodsmentioning
confidence: 91%